The Social(ist) Pedagogies of the MST: Towards New Relations of Production in the Brazilian Countryside - Rebecca Senn Tarlau (Education Policy Analysis Archives, 2013)
This article explores the social(ist) pedagogies of the Brazilian Landless Workers Movement (MST), a large agrarian social movement that fights for socialism in the Brazilian countryside, meaning that workers own their own means of production and collectively produce the food and other products necessary for their communities’ survival. Over the past three decades, activists in the movement have developed an alternative educational proposal for rural schooling that supports these new social relations of production. Drawing on major theories of reproduction, cultural production, and resistance in the field of education, I argue that three theorists—Paul Willis, Paulo Freire, and Antonio Gramsci—are critical in assessing the role of schools in processes of social reproduction. I examine four components of the MST’s social(ist) pedagogy: the incorporation of manual labor into public schools; the promotion of collective learning; counter-cultural production; and linking schools to concrete political struggles. Drawing on Willis, Freire, and Gramsci, I argue that the MST’s educational proposal is a limited but real attempt to interrupt dominant social relations of production in the Brazilian countryside, thus representing a unique example of social pedagogy in the 21 century.